Interference: Its Role in the Second or Foreign Language Mastery to Indonesian Learners - Mahmud, Mahmud (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2017)
Language development is always influenced by economic, social, politic, culture and science. The influencing between languages appears in the form of using words or phrases interchangeably in both oral and written form.Interference is caused by speaker bilingualism background, disloyalty to target language, the limited vocabularies of TL mastered by a learner, Need of synonym, Prestige and style.Interference can be a negative type of language transfer, like the use of a native-language pattern or role which leads to an error or inappropriate form in the target language. In the other hand, it is also positive transfer, as it makes the learning easier, and may occur when both native language and the target language have similar form. Events of interference has four types; phonic interference, grammatical interference, lexical interference and semantic interference Keywords: Language development, Interference, language transfer